THE ROLE OF EMPLOYEE ENGAGEMENT ON JOB SATISFACTION AND ITS EFFECT ON ORGANIZATIONAL PERFORMANCE - Noercahyo, Unggul Sentanu; Maarif, Mohammad Syamsul; Sumertajaya, I Made (Jurnal Aplikasi Manajemen, 2021)
The purpose of this research was to analyze the role of employee engagement from the perspective of job engagement and organization engagement on job satisfaction and its effect on organizational performance. This research was conducted at a multinational manufacturing chemicals company located in Tangerang and Cilegon. The population was approximately 121 employees consisting of three job levels: Manager, White Collar, and Blue Collar. A target sample determined approximately 93 employees. Sampling using a non-probability sampling approach with a quota sampling method. The questionnaire was distributed to the population, but only 86 respondents filled out and returned the questionnaire. Method of hypothesis testing using Partial Least Square of Structural Equation Modeling (PLS-SEM) approach. The results suggested that job engagement has a positive and significant effect on job satisfaction but does not significantly affect organizational performance. Next, organization engagement has a positive and significant effect on job satisfaction but does not significantly affect organizational performance. Furthermore, job satisfaction has a positive effect and significantly influences organizational performance. Future research is advisable to examine the relations of other variables such as workload, work-life balance, and implementation of an integrated management system, which, believed, can provide a comprehensive view of employee engagement, job satisfaction, and organizational performance.